Volcanological aspects of the northwest region of Parana continental flood basalts (Brazil) - Braz Machado, F.; Reis Viana Rocha-Junior, E.; Soares Marques, L.; Ranalli Nardy, A. J. [UNESP] (Copernicus Gesellschaft Mbh, 2015)
There has been little research on volcanological aspects of Parana continental flood basalts (PCFBs), and all investigations have mainly been concentrated on the internal portions of the lava flows. Thus, this study describes for the first time morphological aspects of lava flows and structural characteristics caused by lava-sediment interaction in the northwestern PCFB province (NW-PCFB). Early Cretaceous (134 to 132 Ma) tholeiitic rocks of the PCFB were emplaced on a large intracratonic Paleozoic sedimentary basin (Parana Basin), mainly covering dry eolian sandstones (Botucatu Formation). As this sedimentary unit is overlain by the basic lava flows of the PCFB, the interaction of lavas and unconsolidated sediments resulted in the generation of fluidal peperites. This aspect is significant because it shows that restricted wet environments should have existed in the Botucatu desert. The peperite zones of the NW-PCFB are associated with compound pahoehoe-type (P-type) flows and are always related to the first volcanic pulses. These flows have dispersed vesicles and sand-filled cracks in their base and top borders, as well as the presence of interlayered sandstones with irregular contacts and varied thicknesses. It is remarkable that, to the best of current knowledge, only in this area of the whole PCFB did the volcanic activity start with low-Ti basalt flows of Ribeira type (TiO2 < 2.3 wt%), which are scarce in the province.